Creative Cognitive Processes in Higher Education. (20th November 2014) - Miller, Angie L.; Dumford, Amber D.
Abstract: This paper explores whether or not students in higher education settings are using creative cognitive processes, how these processes are related to deep approaches to learning, and in what types of settings and students these processes are most prevalent. Data collected from 8, 724 students at 17 institutions participating in the 2010 National Survey of Student Engagement suggests that first‐year and senior students employ several different creative cognitive processes in their everyday activities. Results from exploratory and confirmatory factor analyses suggest two distinct types of processes: deliberate creative processes and intuitive cognitive processes. Additional analyses indicate significant positive relationships between both types of creative processes and deep approaches to learning, as well as statistically significant differences in the use of creative processes based on gender, enrollment type, and type of institution. Potential reasons for and implications of these findings are discussed.